Telling women's lives : the new biography - Wagner-Martin, Linda (Rutgers University Press, 1994)
Placing herself in the avid reader's chair, Linda Wagner-Martin writes about women's biography from George Eliot and Virginia Woolf to Eleanor Roosevelt and Margaret Mead, and even to Cher and Elizabeth Taylor. Along the way, she looks at dozens of other life stories, probing at the differences between biographies of men and women, prevailing stereotypes about women's lives and roles, questions about what is public and private, and the hazy margins between autobiography, biography, and other genres. In quick-paced and wide-ranging discussions, she looks at issues of authorial stance (who controls the narrative? who chooses which story to tell?), voice (is this story told in the traditional objective tone? and if it is, what effect does that telling have on our reading?), and the politics of publishing (why aren't more books about women's lives published? and when they are, what happens to their advertising budgets?).